BUDAYA ORGANISASI DALAM PERSPEKTIF GOOD CORPORATE GOVERNANCE - Siti Nurhaliza; Dewarni Siregar; Habibul Akhir; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Organizational culture is a fundamental element that plays a crucial role in supporting the effectiveness of organizational governance, particularly in the implementation of Good Corporate Governance (GCG) principles. Organizational culture not only reflects the values and norms adopted by an organization but also shapes the behavior, attitudes, and decision-making patterns of its members. This study aims to examine the concept of organizational culture, its existence within organizations, as well as its objectives and functions in improving organizational performance and effectiveness. The research method employed is a literature review by analyzing relevant books and scientific journals related to organizational culture and GCG. The findings indicate that a strong, adaptive, and ethically grounded organizational culture is capable of creating internal stability, enhancing employee commitment, and supporting the implementation of good governance practices. Therefore, strengthening organizational culture is a strategic necessity in realizing sustainable and integrity-based organizations.